RARE EARTH ELEMENTS IN ZONAL METAMORPHIC MINERALS - Skublov S.G.; Drugova G.M. (My University, 2004)
The REE distribution in zonal metamorphic minerals (garnet, amphibole, and clinopyroxene) was studied on an ion microprobe. Zoning of the metamorphic garnets indicates that the HREE contents increase and LREE contents decrease with increasing temperature. The amount of MREE remains virtually unchanged, and this testifies to variable REE mobility in the metamorphic process. Garnets from rocks of similar composition have analogous REE patterns, which provides evidence for an equilibrium REE distribution in garnet. Garnets from the gneisses are characterized by a strongly fractionated REE pattern enriched in HREE and having a negative Eu anomaly. Garnets from the metasomatic rocks are depleted in REE relative to those from the metamorphic rocks and reveal distinct zoning of grains with an outward decrease in the REE sum and the absence of an Eu anomaly. Garnet grains with an obvious discrepancy between their retrograde major-element zoning and prograde REE zoning are most informative with respect to the metamorphic history. When garnet is metasomatically replaced by amphibole, the latter inherits the REE pattern of garnet. The retrograde alteration of amphibole results in the development of REE zoning with depletion in all REE. The REE sum decreases in both amphibole and clinopyroxene in response to lower temperature metamorphic conditions.